2019
DOI: 10.1002/lsm.23176
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Erythematotelangiectatic Rosacea With Pulsed‐Dye Laser and Oxymetazoline 1.0% Cream: A Retrospective Study

Abstract: Background and Objectives: Pulsed-dye laser (PDL) and oxymetazoline 1.0% cream are each used for the treatment of erythematotelangiectatic (ET) rosacea. PDL targets oxyhemoglobin and can reduce facial erythema and telangiectasias. Oxymetazoline 1.0% cream is an α adrenergic agonist, which has shown to reduce facial erythema. The aim of this study was to determine the degree of erythema improvement and telangiectasia clearance after combination treatment with PDL plus oxymetazoline 1.0% cream. Study Design/Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 15 publications
1
30
0
Order By: Relevance
“…The findings of a phase 4, multicenter, interventional, open-label study with 46 patients suggest the benefit of oxymetazoline as adjunctive therapy with energy-based therapy for the treatment of moderate to severe persistent facial erythema associated with rosacea [54]. A retrospective study including 31 subjects revealed that the combination of pulsed dye laser and 1.0% oxymetazoline cream reduced erythema and telangiectasias both safely and effectively [55]. An open-label study including 21 subjects assessed the efficacy and tolerability of topical skin care and sun protection combined with IPL therapy [56].…”
Section: Laser-and Light-based Therapiesmentioning
confidence: 99%
“…The findings of a phase 4, multicenter, interventional, open-label study with 46 patients suggest the benefit of oxymetazoline as adjunctive therapy with energy-based therapy for the treatment of moderate to severe persistent facial erythema associated with rosacea [54]. A retrospective study including 31 subjects revealed that the combination of pulsed dye laser and 1.0% oxymetazoline cream reduced erythema and telangiectasias both safely and effectively [55]. An open-label study including 21 subjects assessed the efficacy and tolerability of topical skin care and sun protection combined with IPL therapy [56].…”
Section: Laser-and Light-based Therapiesmentioning
confidence: 99%
“…However, retrospective and preclinical studies have investigated the efficacy of combining oxymetazoline treatment with PDL therapy. A retrospective study analyzed pretreatment and posttreatment images from 31 patients with rosacea treated with oxymetazoline and PDL at two dermatologic surgery practices [16]. After an average of 4 months of daily oxymetazoline treatment and two PDL treatments, 55% (17/31) of patients demonstrated at least a one‐grade improvement in CEA, and 41% of patients (12/29) demonstrated 50–75% clearance of telangiectasias among patients with telangiectasias at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…3 Use of oxymetazoline as adjunctive therapy with potassium-titanyl-phosphate (KTP) lasers, 595nm pulse dye laser (PDL), and IPL has been demonstrated to be well tolerated and efficacious in further helping to reduce facial erythema. 12 , 13 …”
Section: Topical Medical Therapiesmentioning
confidence: 99%